2017
DOI: 10.7755/fb.115.4.9
|View full text |Cite
|
Sign up to set email alerts
|

The physiological stress response, postrelease behavior, and mortality of blacktip sharks (Carcharhinus limbatus) caught on circle and J-hooks in the Florida recreational fishery

Abstract: Abstract-The blacktip shark (Carcharhinus limbatus) is the most commonly captured species in the Florida recreational shark fishery. We aimed to quantify the postrelease mortality of blacktip sharks and to determine whether hook type (circle or J) had any impact on survival. We measured capture variables (e.g., fight time, animal condition, etc.), blood gas analytes, and finescale behavior obtained by using acceleration data loggers for blacktip sharks (n=31) caught on rod and reel by recreational fishermen. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 22 publications
9
26
2
Order By: Relevance
“…Consequently, it has been suggested that blacktip sharks could lack the mechanisms (e.g., splenic red blood cell ejection and red blood cell swelling through Na + -H + exchangers; Nikinmaa, 1992;Brill et al, 2008) responsible for maintaining or increasing oxygen delivery during strenuous activity . Although the results of this research indicate that blacktip sharks may be particularly sensitive to the stress associated with capture, Whitney et al (2017) found a relatively low rate of PRM in the recreational fishery for blacktip sharks in the Gulf of Mexico. Additional data are needed on both the physical and physiological effects of recreational rod-and-reel capture on the blacktip shark, and how these effects influence PRM.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…Consequently, it has been suggested that blacktip sharks could lack the mechanisms (e.g., splenic red blood cell ejection and red blood cell swelling through Na + -H + exchangers; Nikinmaa, 1992;Brill et al, 2008) responsible for maintaining or increasing oxygen delivery during strenuous activity . Although the results of this research indicate that blacktip sharks may be particularly sensitive to the stress associated with capture, Whitney et al (2017) found a relatively low rate of PRM in the recreational fishery for blacktip sharks in the Gulf of Mexico. Additional data are needed on both the physical and physiological effects of recreational rod-and-reel capture on the blacktip shark, and how these effects influence PRM.…”
contrasting
confidence: 70%
“…Blood samples (3 mL) were drawn by using 18-gauge, sterilized needles and heparin-rinsed syringes, and samples were immediately injected into 10-mL vacutainers that contained sodium heparin. To avoid compromising accuracy of blood gas analysis after phlebotomy (Whitney et al, 2017), a subsample of whole blood (90 μL) was immediately (within 30 s) analyzed for pH and lactate by using an i-STAT 3 portable blood analyzer (Zoetis Inc., Parsippany-Troy Hills, NJ) with a CG4+ cartridge (Zoetis Inc.). This analyzer has been used in prior field studies on elasmobranch species (e.g., Brooks et al, 2012;Gallagher et al, 2014), and the relative accuracy of measurements of pH and lactate in ectothermic sharks has been validated (Gallagher et al, 2010;Harter et al, 2015).…”
Section: Blood Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the extent and manner in which the sharks responded to tidal flow, we generated animations of each shark track overlaid on a map of coinciding current vectors in the San Francisco Bay (https://doi.org/10.6084/m9.figshare.5791503). While some studies (e.g., Whitney et al 2017) suggest that it may be appropriate to remove the portion of the track immediately after capture and release to account for the behavioral effects of capture stress, we found that the number of times the sharks moved into and out of the bay in the first twenty hours of tracking (n = 6) proportionally reflected what we observed in the following twenty-four "or more"hours (n = 9). Thus, in order to maximize the movement data available to properly explore the use of hydrodynamic models in this context, we used the entirety of each shark track in the analysis.…”
Section: Data Processingcontrasting
confidence: 41%
“…Mandelman & Skomal 2009, Marshall et al 2012, Butcher et al 2015, Dapp et al 2016b). In recent years, studies examining the physiological responses and post-capture behaviour of elasmobranchs, particularly sharks, have expanded from a common set of commercially relevant species subjected to longline fishing (Dapp et al 2016a) to work on coastal species under recreational and fishery-independent contexts (Danylchuk et al 2014, Gallagher et al 2017a, Whitney et al 2017, Jerome et al 2018, coral reef-dwelling species (Dapp et al 2017), polar settings (Barkley et al 2017), and even the deep sea (Talwar et al 2017). In addition to advancing our understanding of the comparative physiology of elasmobranchs, this research provides managers, fishers, and the general public with relevant information to address targeted conservation problems, should they occur.…”
Section: Introductionmentioning
confidence: 99%